Synthesis and single-molecule magnet properties of a trimetallic dysprosium metallocene cation. Issue 52 (4th June 2021) - He, Mian; Guo, Fu-Sheng; Tang, Jinkui; Mansikkamäki, Akseli; Layfield, Richard A.
Abstract : The first trimetallic dysprosocenium single-molecule magnet is described. This material signposts a polycationic dysprosium metallocene SMM with properties that could surpass those of leading systems. Abstract : The dimetallic fulvalene-bridged dysprosium complex [Dy(Cp*)(μ-BH4 )2 (Fv tttt )] (1, Cp* = C5 Me5 ) is converted into the trimetallic borohydride-bridged species [Dy(Cp*)(Fv tttt )2 Dy(μ-BH4 )3 ] (2). In turn, 2 is reacted with a silylium electrophile to give [Dy(Cp*)(μ-BH4 )(Fv tttt )2 Dy][B(C6 F5 )4 ] ([3][B(C6 F5 )3 ]), the first trimetallic dysprosocenium cation. Compound [3 ][B(C6 F5 )3 ] can also be formed directly from 1 by adding two equivalents of the electrophile. A three-fold enhancement in the effective energy barrier from 2 to 3 is observed and interpreted with the aid of ab initio calculations.